THE TRANSLATOR'S VOICE IN THE TRANSLATED VERSION OF MICHAEL SCOTT'S THE SORCERESS: THE SECRET OF THE IMMORTAL NICHOLAS FLAMEL - Purnama, Bayu Surya (2013)
The present study entitled The Translator's Voice in The Translated Version of Michael Scott's The Sorceress: The Secret of The Immortal Nicholas Flamel is a content analysis of Michael Scott's translated novel by Mohammad Baihaqi focusing on the translator's voice. The discussion focuses on the strategies which are used by the translator to contribute his voice. Therefore, the discussion is framed within the theories of translation strategies (Venuti, 2010) and the translator's voice in translated narrative (Hermans, 2010). The study utilizes a qualitative method particularly content analysis. The result of the present study shows that three most frequent strategies used by the translator are preservation, omission and addition. The study also discovers that the translator contributes his voice mostly through two cases; case of self-reflexiveness and self-referentiality and case of contextual overdetermination. The study shows that the translator has his voice visible through the use of strategies in foreignization and in the cases above since it may be seen necessary to accommodate the novel's culture in the target language.